2017
DOI: 10.22201/iibi.0187358xp.2017.71.57815
|View full text |Cite
|
Sign up to set email alerts
|

Patentes mexicanas del Distrito Federal: caracterización por delegación y área tecnológica (2009-2012)

Abstract: El objetivo de este trabajo es estudiar la dinámica de las patentes otorgadas en México a residentes mexicanos ubicados en el Distrito Federal. Se entiende en este trabajo que las patentes dan muestra de la capacidad inventiva y son un elemento que impulsa las actividades de innovación en las empresas. El estudio se realiza como un aporte al desarrollo de políticas públicas encaminadas a la protección intelectual y a la innovación. Se encuentra que el Distrito Federal concentra casi la mitad de las patentes ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…[ 61 ] and Meza-Rodríguez et al . [ 62 ], have examined patenting activity among Mexican inventors. Specifically, Aboites and Díaz [ 60 ] analyzed patenting behavior and observed patterns in the relationships between Mexican inventors and multinational companies.…”
Section: Theoretical Basis For the Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…[ 61 ] and Meza-Rodríguez et al . [ 62 ], have examined patenting activity among Mexican inventors. Specifically, Aboites and Díaz [ 60 ] analyzed patenting behavior and observed patterns in the relationships between Mexican inventors and multinational companies.…”
Section: Theoretical Basis For the Present Studymentioning
confidence: 99%
“…For their part, Meza-Rodríguez et al . [ 62 ] focused on patenting activity at the local level in Mexico City. The results showed that in that jurisdiction nearly half of the patents granted were assigned to inventors who are Mexican residents, for inventions primarily classified as of a medium to high technological level.…”
Section: Theoretical Basis For the Present Studymentioning
confidence: 99%